STARTEGI POLITIK HASBULLAH LAPER MAKING DALAM PEMILIHAN UMUM LEGISLATIF DPRD DI KABUPATEN LEMBATA (DAPIL III) PERIODE 2024-2029 - Ledo, Gabriel (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study examines the political marketing strategies used by Hasbullah Laper Making, in winning the legislative elections at the district level in Lembata Regency in 2024. This study aims to identify and analyze effective political strategies in winning voter support, as well as understanding the factors that influence this success. The theory used in this study is the theory of Firmanzah explaining that in political strategy there are three methods or ways that political parties and candidates use to win the general election: the strategy of instilling confidence, the strategy of strengthening, and the strategy of introducing and capturing. This research is a qualitative descriptive study, aimed at identifying the political marketing strategies employed by Deasy Ballo Foeh in winning the general election in Kupang Regency. Data were collected through interviews, observation, and documentation. The results indicate that Hasbullah's Laper Making strategy of gaining recognition and winning votes focused on a personal approach, active involvement in community life, and the implementation of concrete programs tailored to the needs of the community. Through direct communication, sincere interactions, and a simple and popular image, Hasbullah succeeded in building emotional closeness with the community, especially with farmers, traditional leaders, religious leaders, and young voters. Family influence, particularly his father's strong social standing, also strengthened public trust in him. The electoral strengthening strategy was implemented through a community-based approach, optimizing social networks, and utilizing his economic and cultural capital